2011
DOI: 10.2133/dmpk.dmpk-10-rg-127
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Cibenzoline-Induced Hypoglycemia in Rats

Abstract: Hypoglycemia is one of the serious adverse effects induced by cibenzoline (CBZ), an antiarrhythmic agent. In order to clarify the pharmacodynamics of CBZ-induced hypoglycemia, CBZ was administered intravenously to conscious rats at a dose of 5, 10 or 20 mg/kg and serum samples were collected periodically to determine the concentrations of CBZ, insulin and glucose. The pharmacokinetics of CBZ showed nonlinear characteristics and could be described by a two-compartment model with Michaelis-Menten elimination kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, the estimated glucose half-life (approximately 10.2 min) calculated by the k in,Glu /C Glu(0) value in the present study was similar to previously reported values (approximately 15.6-43.8 min). [33][34][35] Thus, under conditions in which the glucose-induced secretion of insulin and effects of insulin on glucose utilization are not impaired, a simple model such as ours appears to be sufficient to describe the kinetics of glucose.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the estimated glucose half-life (approximately 10.2 min) calculated by the k in,Glu /C Glu(0) value in the present study was similar to previously reported values (approximately 15.6-43.8 min). [33][34][35] Thus, under conditions in which the glucose-induced secretion of insulin and effects of insulin on glucose utilization are not impaired, a simple model such as ours appears to be sufficient to describe the kinetics of glucose.…”
Section: Discussionmentioning
confidence: 92%
“…This provides a potential mechanism for cibenzoline-induced hypoglycaemia. 21,22 Unfortunately, we did not implement insulin measurement in this case, but these proposed mechanisms may explain the occurrence of hypoglycaemia in our patient, despite maintaining cibenzoline blood concentrations within the therapeutic range.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, it is known that this medicine functions as an ATP-sensitive potassium (KATP) channel blocker and thereby facilitates endogenous insulin secretion from pancreatic β-cells, which can lead to the onset of hypoglycemia (4,5). We herein report two frail, late-stage elderly subjects who experienced a severe and prolonged hypoglycemic coma after the administration of CZ.…”
Section: Introductionmentioning
confidence: 99%